BOOSTING STUDENTS’ VOCABULARY MASTERY IN THE PANDEMIC ERA USING PROJECT BASED LEARNING VIDEO - Dewa Gede Krishnadana; Putu Kerti Nitiasih; Luh Gd Rahayu Budiarta (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2021)
One of the essential things in English besides writing, speaking, listening, and reading and skills is vocabulary. Vocabulary was one of the essential things that must be mastered in order to be able to master the other four essential skills. The use of project-based learning-based learning videos can be a solution in improving students' vocabulary skills. The study aimed to determine the video used as a learning media in boosting students’ vocabulary skills in the pandemic era. The current research utilized a quasi-experimental design. The group which given the pre-test and post-test scenarios were treated as a control group. The group got two different treatments at once. The subject was primary school students in fifth grade. To collect the data, the instruments used included video, pre-test, and post-test. All data obtained were calculated using the SPSS 20 version. Data statistics revealed that the mean score was improved from the pre-test (63.23) to the post-test (84.52). After the normality and homogeneity test, the data obtained were categorized as standard and homogeny. In addition, according to the data analysis, the null hypothesis was rejected, which means that the use of educational learning video was very effective for boosting and improving students’ vocabulary skills.